St. Hilary Of Poitiers On The Christocentrism Of The Spiritual Interpretation Of The Holy Scriptures - Stanula, Emil (Studia Theologica Varsaviensia, 2020)
Two general remarks arise from the synthetic interpretation of the biblical christocentrism presented by Saint Hilary. e first concerns the subject of theological study and biblical studies. e above-mentioned presentation of the arguments of Hilary implies that the mystery of Christ manifesting itself in history, of which he is the creator and interpreter at the same time, constitutes the essence of theology and exegesis. e biblical senses, considered as the result of biblical and theological research and study, in this approach are nothing but different aspects of incomprehensible mystery of Christ. Because the mystery of Christ is revealed in history and is history itself, therefore the theological and exegetical study is of a historical nature at least in the sense that this mystery can be recognized by applying the aspect-oriented method by comparing what is contained in the Scriptures with what people are currently experiencing in a particular episode of history, because the creator of the latter is Christ. One could say that it seems to follow from the last statement, that for Saint Hilary, there are no rigid forms of dogmas established once and for all but one: the incomprehensible mystery of Christ. Although always and everywhere studied, it will never be understood and expressed in words. In the act of studying it, a person constantly extracts new aspects from it. It is the task of the exegete and theologian to update it, to make the faithful acquainted with the complexity of its message. If ordinary believers do this even at liturgical meetings, then, according to Hilary, even though they have not completed specialist theological and biblical studies, they can read and interpret the holy text fruitfully. e second remark indicates the conditions sine qua non of the existence and operation of the theologian, exegete, no matter if he is a specialist or an ordinary faithful. ese conditions are faith in Christ and perservance in participation in the Christological reality of the Church and the community of the faithful. e above claim does not undermine the value of biblical and theological studies – as understood by us in terms of erudite knowledge. Scholarly biblical commentaries and the theological and historical writings of Saint Hilary can be regarded as the denial of such a conclusion. e Bishop of Poitiers, by encouraging his readers – by his own example – to intellectual and moral preparation for the study of the Scriptures, also emphasizes the pointlessness of practicing exegesis and theology if it is not accompanied by faith in Christ, in isolation from tradition, the continuity of history, finally in isolation from the community of the members of Church.